Penerapan Metode Weighted Product Untuk Pemilihan Lokasi Lahan Baru Pemakaman Muslim Dengan Visualisasi Google Maps - Heliza Rahmania Hatta; Muhammad Rizaldi; Dyna Marisa Khairina (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2016)
Abstract—Difficulty to find space for graveyard for Muslim causes the old cemetery getting crowded. The determination of the land suitability is very crucial for involved decision makers in this case the Regional Government. If not done properly and presicely, an error in land allocation will often cause various problems. Decision Support System can be used to help people to make decisions. Weighted Product Method is a very effective method because the required time for the calculation is much shorter. The purpose of this research is to make the electoral system of prospective new cemetery land for Muslim in Samarinda. It is hoped the system can help the Department of Hygiene and gardening of Samarinda in the process of determining the location of a new cemetery land in Samarinda. Has produced a new system of cemetry land site selection for Muslims using the Weighted Product is supported with visualization google maps. Google maps with visualization make it easier for users to find out information on the location of prospective new cemetery land.